A report of two atypical genetic cases of cherubism: Reduced penetrance and sporadic occurrence. Issue 2 (March 2021) - AlAli, Ahmad M.; Dashti, Hussain; Al-Yahya, Yahya; Ali, Hamad
Abstract: Cherubism is a rare inherited disorder involving the jaws exclusively and mainly seen in the pediatric population. It has distinctive clinical features and shares radiographic and histopathologic characteristics with other fibro-osseous lesions. Cherubism is caused by a mutation in the SH3BP2 gene located on chromosome 4. Two atypical genetic cases of cherubism from different families that associated with SH3BP2 gene point mutations c.1253C > A and c.1258 G > A in exon 9 were reported. The first case, a 7 years old boy, showed reduced penetrance as the father who is carrying the same mutation did not show any phenotypic features of cherubism. While in the second case, a 6 years old boy, both of his parents proved to be negative for the mutation. Hence the mutation of the child has occurred sporadically. Although the disease seems to be a simple monogenic disease characterized by specific features, a varied genetic presentation can be expected. Understanding such potential influence could highlight possible therapeutic intervention for cherubism.